A Rare Report of Carbapenem Resistant Vibrio fluvialis Isolated from a case of Walled off Necrosis: A Sequelae of Acute Necrotising Pancreatitis - P Ganesh Perumal; L Venkatakrishnan; B Appalaraju; R Rajakumar; R Someshwaran (Journal of Clinical and Diagnostic Research)
Vibrio fluvialis (V. fluvialis) is commonly found in coastal environments and is an emerging pathogen encountered in diarrhoeal outbreaks and sporadic extraintestinal cases. V. fluvialis infections usually manifest as watery bloody diarrhoea, nausea, vomiting, gastroenteritis and peritonitis. In this case report, an unusual presentation of Multidrug Resistant (MDR) V. fluvialis along with Klebsiella pneumoniae co-infection from a case of Walled Off Necrosis (WON)- A complication of Acute Necrotising Pancreatitis (ANP) is discussed. The patient presented with the acute abdomen and had peripancreatic collection for which Ultrasound (USG) guided 12F pigtail drain placed over the right lower quadrant of the abdomen and conservatively managed. Routine cultures were done and the growth on Sheep Blood Agar (SBA) plate and MacConkey (MAC) agar plates were subjected for automated phenotypic identification by Matrix Assisted Laser Desorption Ionisation Time of Flight-Mass Spectrometry (MALDITOF-MS) and Vitek-2 systems and was identified as V. fluvialis. Also, molecular tests like 16S rRNA Polymerase Chain Reaction (PCR) followed by Sanger’s sequencing was done and the identification was further confirmed. Phenotypic RESIST-5 TRURAPID O.K.N.V.I. commercial lateral flow immunochromatographic assay for detection of clinically relevant and common carbapenemase genes like NDM, OXA-48, VIM, IMP and KPC was done which revealed this V. fluvialis isolate as New Delhi Metallo betalactamase (NDM) type of Carbapenemase producer. Patient was managed with levofloxacin and doxycycline and patient condition improved and was discharged.